2018
DOI: 10.1038/s41598-018-25707-y
|View full text |Cite
|
Sign up to set email alerts
|

Virulent PB1-F2 residues: effects on fitness of H1N1 influenza A virus in mice and changes during evolution of human influenza A viruses

Abstract: Specific residues of influenza A virus (IAV) PB1-F2 proteins may enhance inflammation or cytotoxicity. In a series of studies, we evaluated the function of these virulence-associated residues in the context of different IAV subtypes in mice. Here, we demonstrate that, as with the previously assessed pandemic 1968 (H3N2) IAV, PB1-F2 inflammatory residues increase the virulence of H1N1 IAV, suggesting that this effect might be a universal feature. Combining both inflammatory and cytotoxic residues in PB1-F2 enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…However, PB1-F2 has dissimilar functions in different virus types/subtypes and hosts, which are determined by its length. Usually, avian influenza viruses have full-length PB1-F2 protein, enabling all functions [44], while classical swine H1N1 and A(H1N1)pdm09 viruses frequently contain truncated PB1-F2 with associated loss of function as seen in TJ/1606/18.…”
Section: Discussionmentioning
confidence: 99%
“…However, PB1-F2 has dissimilar functions in different virus types/subtypes and hosts, which are determined by its length. Usually, avian influenza viruses have full-length PB1-F2 protein, enabling all functions [44], while classical swine H1N1 and A(H1N1)pdm09 viruses frequently contain truncated PB1-F2 with associated loss of function as seen in TJ/1606/18.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for the differences in levels of IL-1β production is the ability for activation of the inflammasome complex upon recognition of viral antigen, such as PB1-F2 ( McAuley et al, 2013 ). Interestingly, the inflammasome activation-associated mutation site 79R was observed in the PB1-F2 of all five H9N2 viruses except Hu/04 virus ( Alymova et al, 2018 ) ( Table 1 ). Our results indicated that even LPAI H9N2 viruses replicated well in mice and chickens, and could cause significant increases in pro-inflammatory cytokine expression ( Figure 4A , 5D ).…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Both subtypes and clades probably have intrinsic differences in virulence; for example, due to different receptor preferences or differences in virulenceassociated pro teins. [58][59][60] However, such variations are difficult to distinguish from the effects of immunity acquired through prior infection or vaccination.…”
Section: Diversity Of Influenza Virusesmentioning
confidence: 99%